The republic of numbers unexpected stories of mathematical Americans - Roberts, David Lindsay (Johns Hopkins University Press, 2019)
"This book tells the story of how America changed from a nation devoid of mathematical interest and expertise into a powerhouse of thinkers. The story is told chronologically, with one example pulled from each decade; these chapters reveal pivotal moments in America's mathematical maturation and feature a diverse cast of historical figures"--